Habenaria diphylla (Nimmo) Dalzell: A new addition to the Orchid flora of Bilaspur district (C.G), Central India - A.K. Dixit, S. Vinodia (Current Botany, 2017)
Habenaria diphylla (Nimmo) Dalzell , reported as a new record Â to the orchid flora of Â Bilaspur district of Achanakmar-Amarkantak Biosphere Reserve (Central India) . Brief description, illustrations and ecology are provided.